2007
DOI: 10.1104/pp.107.104588
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Nucleotide-Binding Site-Leucine-Rich Repeat Genes in the Model Plant Medicago truncatula  

Abstract: The nucleotide-binding site (NBS)-Leucine-rich repeat (LRR) gene family accounts for the largest number of known disease resistance genes, and is one of the largest gene families in plant genomes. We have identified 333 nonredundant NBS-LRRs in the current Medicago truncatula draft genome (Mt1.0), likely representing 400 to 500 NBS-LRRs in the full genome, or roughly 3 times the number present in Arabidopsis (Arabidopsis thaliana). Although many characteristics of the gene family are similar to those described… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
288
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(312 citation statements)
references
References 84 publications
24
288
0
Order By: Relevance
“…Every chromosomal rearrangement breakpoint is associated with one or more R genes or mapped resistances. Previously, it has been shown that genomic rearrangement and duplication are significant sources of R-gene dispersal and duplication, which is further complicated by ancestral polyploids (Baumgarten et al 2003;Ameline-Torregrosa et al 2008). Increased sequence information will provide resolution of the precise relationship of R-gene clusters, embedded transposons, and chromosome breakpoints that may be detected in comparisons between related genera.…”
Section: Discussionmentioning
confidence: 99%
“…Every chromosomal rearrangement breakpoint is associated with one or more R genes or mapped resistances. Previously, it has been shown that genomic rearrangement and duplication are significant sources of R-gene dispersal and duplication, which is further complicated by ancestral polyploids (Baumgarten et al 2003;Ameline-Torregrosa et al 2008). Increased sequence information will provide resolution of the precise relationship of R-gene clusters, embedded transposons, and chromosome breakpoints that may be detected in comparisons between related genera.…”
Section: Discussionmentioning
confidence: 99%
“…A diverse set of 1,120 protein sequences from the highly conserved NBS domain was built from a panel of cloned legume NBS sequences (B.D.R., unpublished data), as well as published NBS domains from Mt1.0 and Poplar 43,44 . These sequences were used as a TBLASTN query against CaGA v1.0 to identify all NBS genomic regions.…”
Section: Identification and Phylogenetic Analysis Of Nbs-lrr Genesmentioning
confidence: 99%
“…Among all known types of R genes, nucleotide-binding site-leucine-rich repeat (NBS-LRR, NBS for short) genes represent the largest class, encompassing more than 80% of the characterized R genes (Meyers et al, 1999;Meyers et al, 2005;McHale et al, 2006;Friedman and Baker, 2007). Since the first comprehensive study on NBS genes in Arabidopsis (Arabidopsis thaliana; Meyers et al, 2003), NBS genes have been surveyed across various plant genomes, most of which belong to the rosid lineage of eudicots and the Poaceae of monocots (Monosi et al, 2004;Zhou et al, 2004;Yang et al, 2006;Ameline-Torregrosa et al, 2008;Yang et al, 2008;Mun et al, 2009;Porter et al, 2009;Li et al, 2010;Zhang et al, 2011;Lozano et al, 2012;Luo et al, 2012;Andolfo et al, 2013;Shao et al, 2014).…”
mentioning
confidence: 99%
“…Because most nTNL genes encode a coiled-coil (CC) domain at the N terminus, the nTNL genes often are called CC-NBS-LRR (CNL) genes (Meyers et al, 2003;Ameline-Torregrosa et al, 2008). However, recent studies have revealed that apart from CNL genes, a small group of nTNL genes that possess a special N-terminal domain, RPW8 (resistance to powdery mildew8) domain, likely represent a distinct class of NBS genes (RPW8-NBS-LRR [RNL]; Xiao et al, 2001;Cannon et al, 2004;Bonardi et al, 2011;Collier et al, 2011;Shao et al, 2014;Zhang et al, 2016).…”
mentioning
confidence: 99%